THE ROLE OF THE EAST IN THE LIFE AND CREATIVE ACTIVITY OF L. TOLSTOY (Scientific journal of the Fergana State University, 2023)
The article analyzes the influence of the philosophy of the East on the work of L.Tolstoy. The study of the works of famous philosophers, as well as familiarity with the customs, life and religion of the peoples of the Caucasus were of great importance in the formation of Tolstoy-philosopher. Philosophical treatises, numerous religious and ethical essays, articles, extensive philosophical correspondence all this allows us to consider the personality of Leo Tolstoy himself as an outstanding sage of Russia, recognized throughout the world.